Pemanfaatan Pendaftaran Online (Antrian) Pelayanan Kesehatan dengan Mobile-JKN pada Masyarakat di Provinsi Bali - Wirajaya, Karma Maha (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2025)
The Mobile-JKN application is one form of BPJS Kesehatan innovation that can be accessed via smartphone. This application provides convenience for JKN-KIS participants in obtaining health services. However, in reality, many people still do not know the online registration (queue) feature for health services using Mobile-JKN so that the utilization of Mobile-JKN is still low by the community in accessing health services. The purpose of this study is to determine the determinants of the utilization of online queues for health services with mobile JKN. This study is an analytical study through a cross-sectional approach with research data collection for 2 months. The research sample is the community of mobile JKN users in the province of Bali who meet the inclusion and exclusion criteria. The sample size is 100 respondents and is analyzed using logistic regression. Based on the results of the analysis, all aspects of Performance Experancy, facilitating conditions, social influence, obtained less than good results. In addition, the usefulness of online queues for health services with mobile JKN also showed less than good results, namely 66.4%. Factors that influence the utilization of online queues with mobile JKN are from the aspect of effort expectancy, namely with a p value <0.0001, while the aspects of performance expectancy, facilitating condition and social influence do not affect the utilization of online queues with mobile JKN. The factor that is most related to the utilization of online registration (queue) with mobile JKN is the aspect of effort expectancy.